ANATOMICAL MODELING OF SUPER-, SUB-EYE PATCH AND CHIN OPENINGS IN FRUITS AND NEWBORN (World Science, 2021)
Using modern anatomical methods, 57 preparations of human fetuses 4-10 months and 7 newborns were studied in order to create models of distances of supra-, suborbital and chin openings between themselves and to standard landmarks in fetuses and newborns taking into account their morphometric parameters. The model of the distance from the supraorbital foramen to bregma (Y1): Y1 = β0 + 0.092 x parietal-heel length of the fetus, where β0 :: 2,783, if the age period = 4 months; 3,106 = 5 months; -0.662 = 6 months; 4,728 = 7 months; 2,676 = 8 months; 0.402 = 9 months; -1,727 = 10 months; 9,094 = newborns; model of the distance between the supra- and suborbital foramina (Y2): Y2 = β0 + 0.011 x parietal-heel length of the fetus, where β0 :: 8,147, if the age period = 4 months; 9.086 = 5 months; 10,260 = 6 months; 12,020 = 7 months; 12,129 = 8 months; 15,164 = 9 months; 17,429 = 10 months; 18,808 = newborns; model of the distance between the orbital and chin openings (Y3): Y3 = β0 + 0.002 x parietal-heel length of the fetus, where β0 :: 8.987, if the age period = 4 months; 9,134 = 5 months; 9,892 = 6 months; 12,250 = 7 months; 11,636 = 8 months; 16,755 = 9 months; 17,877 = 10 months; 18,054 = newborns; model of the distance between the chin holes and the lower edge of the mandible (Y4): Y4 = β0 + 0.008 x parietalheel length of the fetus, where β0 :: 0.268, if the age period = 4 months; 0.178 = 5 months; 0.020 = 6 months; -0.152 = 7 months; 0.020 = 8 months; - 0.115 = 9 months; -0.079 = 10 months; -0.039 = newborns; model of the distance between the orbital foramina (Y5): Y5 = β0 + 0.030 x parietal-heel length of the fetus, where β0 :: 5,762, if the age period = 4 months; 5,895 = 5 months; 11,227 = 6 months; 13,793 = 7 months; 11,691 = 8 months; 11,173 = 9 months; 12,633 = 10 months; 14,494 = newborns; model of the distance between the orbital foramina (Y6): Y6 = β0 + 0.008 x parietal-heel length of the fetus, where β0 :: 9,272, if the age period = 4 months; 11,081 = 5 months; 13,467 = 6 months; 16,854 = 7 months; 15,912 = 8 months; 17,653 = 9 months; 22,635 = 10 months; 23,447 = newborns; model of the distance between the chin holes (Y7): Y7 = β0 - 0.014 x parietal-heel length of the fetus, where β0 :: 12,959, if the age period = 4 months; 15,282 = 5 months; 18,117 = 6 months; 23,178 = 7 months; 23,175 = 8 months; 30,496 = 9 months; 32,227 = 10 months; 33,272 = newborns.